Microbial biomass as an antioxidant for tilapia feed - Grassi, Thiago Luís Magnani [UNESP]; Oliveira, Dayse Lícia [UNESP]; Paiva, Natália Mingues [UNESP]; Diniz, Juliana Campos Pereira [UNESP]; Bosco, Anelise Maria [UNESP]; Pereira, Ariana Aparecida Ferreira [UNESP]; Menezes, Amanda Regina Pinatti [UNESP]; Valadares, Taiana Carvalho [UNESP]; Pastor, Rosemeire Conceição Parra [UNESP]; Ciarlini, Paulo César [UNESP]; Gonçalves, Giovani Sampaio; Villarroel, Morris; et al. (Hindawi, 2018)
Microbial biomass (MB) produced by different industries is thought to be a beneficial supplement in fish feed due to high contents of antioxidants and pigments. However, little is known about their impact on fish health. In this experiment, 960 tilapia (26.84 ± 1.03 g) were fed one of eight experimental diets—a control diet with no MB (C), a control diet with vitamin E (VE) and six diets with three types of MB at two concentrations (0.25% and 0.5%): Rubrivivax gelatinosus (RG25 and RG50), Spirulina platensis (SP25 and SP50) and Saccharomyces cerevisiae (SC25 and SC50). Adding MB to diets decreased plasma total oxidant status, malonaldehyde and leucocyte respiratory burst; increased the total antioxidant status; and did not affect the blood biochemical parameters. In flesh, the use of the MB lowered the thiobarbituric acid-reactive substances and increased redness (except for SC) and carotenoid deposition (except SC25). So, it was concluded that the use of the MB provided an antioxidant effect in tilapia blood plasma, decreased lipid oxidation and increased pigmentation and carotenoid deposition in the fish flesh, without imparting a negative impact on the animals’ health.
Keywords: biochemical analysis; carotenoids; colour; leucocyte respiratory burst; lipid oxidation; TBARS